Knowledge and Practice of Patients with Epilepsy on Vehicle Driving and Epilepsy at a Tertiary Neurological Center in Kathmandu - Rajbhandhari, Pravesh; Gajuryal, Sharad Hari; Singh, Matrika; Nepal, Medhawee; Acharya, Samir; Rajbhandhari, Reema; Shrestha, Resha; Dhakal, Sudan; Shrestha, Pranaya; Pant, Basant (Annapurna Journal of Health Sciences, 2024)
Introduction: Patients with epilepsy are instructed to avoid driving to prevent harm to themselves and others. The Motor Vehicle And Transport Act 2049(1993)- Nepal Law Commission regarding driving license Chapter 4/47/C disqualifies driver license to People With Epilepsy. This study aims to find out the Knowledge and Practice of Patients with Epilepsy in vehicle driving at the Tertiary Neurological Center of Kathmandu Nepal. Methods: A Cross-sectional prospective study was conducted among the patients diagnosed with epilepsy who were seeking treatment at Annapurna Neurological Institute and Allied Science (ANIAS). Structured questionnaire was administered among 102 participants regarding knowledge and practice on driving during the study period. All data were entered in MS Excel and descriptive analysis was done using SPSS Version 21. Results: Among 102 participants, 40.1% of participants with epilepsy frequently drive the vehicle whereas 79.4% of participants had encountered accidents due to epilepsy in the past. 56% of the participants could control the vehicle beforehand after they felt an aura of epileptic seizure. Conclusion: This study showed that the majority of the participants didn’t report their epilepsy condition to the driving management department which should be made to improve awareness and education among license applicants and instructors on driving by people with epilepsy. The majority of participants did not have adequate access to information on epilepsy and driving licenses. Legislations on driving by people with epilepsy should be strictly followed.